Administration of adjuvant chemotherapy for stage II-III colon cancer patients: an European population-based study - Babaei, Masoud; Balavarca, Yesilda; Ulrich, Cornelia; Schrotz-King, Petra; Brenner, Hermann (International journal of cancer, 2018)
The advantage of adjuvant chemotherapy (ACT) for treating Stage III colon cancer patients is well established and widely accepted. However, many patients with Stage III colon cancer do not receive ACT. Moreover, there are controversies around the effectiveness of ACT for Stage II patients. We investigated the administration of ACT and its association with overall survival in resected Stage II (overall and stratified by low-/high-risk) and Stage III colon cancer patients in three European countries including The Netherlands (2009-2014), Belgium (2009-2013) and Sweden (2009-2014). Hazard ratios (HR) for death were obtained by Cox regression models adjusted for potential confounders. A total of 60244 resected colon cancer patients with pathological Stages II and III were analyzed. A small proportion (range 9-24%) of Stage II and over half (range 55-68%) of Stage III patients received ACT. Administration of ACT in Stages II and III tumors decreased with higher age of patients. Administration of ACT was significantly associated with higher overall survival in high-risk Stage II patients (in The Netherlands (HR; 95%CI = 0.82 (0.67-0.99), Belgium (0.73; 0.59-0.90) and Sweden (0.58; 0.44-0.75)), and in Stage III patients (in The Netherlands (0.47; 0.43-0.50), Belgium (0.46; 0.41-0.50) and Sweden (0.48; 0.43-0.54)). In Stage III, results were consistent across subgroups including elderly patients. Our results show an association of ACT with higher survival among Stage III and high-risk Stage II colon cancer patients. Further investigations are needed on the selection criteria of Stages II and III colon cancer patients for ACT.
Gesehen am 26.02.2018
Article was first published online on 21 Nov. 2017